Efficiency Analysis of a Combined Cycle with VHTR and VVER Nuclear Reactors; AIP Conference Proceedings; Vol. 2337 : Thermophysical Basis of Energy Technologies (TBET 2020) - Sopeh M. B. Mohamed Bahyeldin (Technical thermal physics and nuclear energy, 2021)
Title screen